2011
DOI: 10.1155/2011/428714
|View full text |Cite
|
Sign up to set email alerts
|

Bartsocas-Papas Syndrome: Unusual Findings in the First Reported Egyptian Family

Abstract: Bartsocas-Papas syndrome (BPS) is an autosomal recessive syndrome with severe craniofacial, limb, and genital abnormalities. As of 2011, 24 published cases and families were registered in the Orphanet Report Series. Compared to other disorders characterized by pterygia, the condition is usually more severe and often lethal: most affected patients die in utero or shortly after birth. We report the first Egyptian family with Bartsocas-Papas syndrome comprising three cases; our proband who was a female infant wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Recently, a consanguineous Egyptian family (BPS3) with one affected and two healthy siblings was referred to us (Figure 3C and Table 1). 18 The 3.5-month-old affected individual had total absence of body hair and multiple pterygia in almost all joints of the body, including shoulders, elbows, wrists, hips, knees, and ankles. A very large and thick popliteal pterygium and severe distortion of both lower limbs was observed.…”
mentioning
confidence: 99%
“…Recently, a consanguineous Egyptian family (BPS3) with one affected and two healthy siblings was referred to us (Figure 3C and Table 1). 18 The 3.5-month-old affected individual had total absence of body hair and multiple pterygia in almost all joints of the body, including shoulders, elbows, wrists, hips, knees, and ankles. A very large and thick popliteal pterygium and severe distortion of both lower limbs was observed.…”
mentioning
confidence: 99%
“…Mothers' genetic testing revealed that she is a heterozygous carrier of the familial RIPK4 variant. A few authors from different countries have reported BPS cases with similar features and various manifestations [1,[4][5][6]. A case study [5] reported on 4 Arab sibs with manifestations of this syndrome and also had some additional traits that included cutis aplasia, widely spaced nipples, low-set umbilicus, and unilateral renal hypoplasia.…”
Section: Discussionmentioning
confidence: 99%
“…There can be widely variable degrees of manifestations with which those carrying the mutation may be affected [4]. Almost all affected babies die in utero or infancy [1, 5]. This reported case from Dubai, United Arab Emirates, had severe craniofacial abnormalities, pterygia of body joints, ambiguous genitalia, imperforate anus, and a dry thick skin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BPS is a rare autosomal recessive disorder characterized by severe congenital malformations, including severe popliteal pterygia, ankyloblepharon, filiform bands between the jaws, cleft lip and palate, syndactyly, and genital malformations. Most of the BPS cases were fatal either in the prenatal or neonatal period (Abdalla & Morsy, 2011; Aslan et al, 2000; Bartsocas & Papas, 1972; Ceylaner et al, 2007; Dolan et al, 2003; Hall et al, 1982; Martinez‐Frias et al, 1991; Massoud et al, 1998; Papadia et al, 1984; Veenstra‐Knol et al, 2003). However, there are reports showing that some individuals have survived into childhood or beyond via intensive medical care (Erturan et al, 2016; Kalay et al, 2012; Mitchell et al, 2012).…”
Section: Introductionmentioning
confidence: 99%